Learning Media Using Qr Code-Based Professional Pdf Flips as an Effort to Improve Students' Concept Understanding in PAI Lessons - Suci Prihatiningtyas; Filla Hidayatul Mar'ah; Dian Kusuma Wardani; Asiyah Lu’lu’ul Husna (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The learning process that is expected in the digital era is the existence of learning interactions that take place in an interesting, up-to-date, efficient, practical and not boring manner. The purpose of this study was to determine the influence and increase in students' understanding of concepts through the implementation of E-Module learning media with QR Code-based Flip PDF Professional in PAI lessons at SMAN Plandaan Jombang. This study used the One Group Pretest-Posttest Design. The population in this study were students of class XI IPS SMAN Plandaan Jombang. The sample in this study was taken from class XI IPS 3 at SMAN Plandaan Jombang. The data collection technique in this study was by giving pre-test and post-test. The research instrument was a multiple choice test with 30 items and 5 description questions. Data analysis was performed using the prerequisite test and the N-gain test. Based on the results of the study, it was shown that the average N-Gain value in this study was 0.51 in the moderate category. The conclusions in this study indicate that the application of E-Module learning media with Flip PDF Professional can improve students' understanding of the concepts of class XI IPS 3 at SMAN Plandaan Jombang.